VALUES OF ENVIRONMENTAL EDUCATION IN THE ISLAMIC VIEW: (Study Of Ar-Rum Verses 41-42) - Nurnaesih Nurnaesih; Nining Syamsi Komariah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This title was chosen by the author because of the many phenomena of environmental damage at this time, especially Indonesia. Many phenomena of environmental change have become a study which makes our minds relate to various disasters which result in a decline in the quality and quantity of nature so that we think by correlating the environmental education process so far. This incident was caused by the actions of irresponsible humans who only care about themselves without knowing the consequences. As caliph, humans have to study and analyze a lot of what has happened on earth. In this study, the author used a literature review study method by collecting data by reviewing various books. Analysis uses content analysis. The results of the research state that damage to nature is caused by humans, with all their behavior towards nature which causes nature to become damaged, exploiting nature without being based on a strong foundation of faith and ultimately using it excessively to fulfill their desires without thinking that all of nature is entrusted to God. Almighty. The values ??in verses 41-42 state that Islam has a theory of the urgency of saving and preserving nature. This concept has not been used optimally and realistically by the people. Islam is a religion that pays close attention to nature and the continuity of life in the world. As a religion of mercy for all of nature, Islam has rules that lead to limited use, preservation of nature and efforts to rehabilitate the damage experienced.